Метод расчета параметров интегральной сотовой сети связи с изолированным разделением каналов - Меликов, А.З.; Фаттахова, М.И.; Велиджанова, Г.М. (Электронное моделирование, 2014)
Предложена новая многопараметрическая схема разделения каналов в интегральной сети сотовой связи. Разработан метод и алгоритм расчета показателей качества обслуживания разнотипных вызовов при использовании этой схемы. Приведены результаты численных экспериментов. Запропоновано нову багатопараметричну схему поділу каналів в інтегральній сітці сотового зв’язку. Розроблено метод і алгоритм розрахунку показників якості обслуговування викликів різного типу при використанні цієї схеми. Наведено результати чисельних експериментів. A scheme for isolated partition of channels in the integral cellular network where voice and data calls are processed is proposed. In accordance to the proposed scheme the voice calls require a free channel in their own zone and, if all channels in this zone are occupied, a free channel in another zone might be assigned only for handover voice calls. There is a threshold parameter for the number of handover voice calls in the zone for data calls. To determine the rule for access of data calls a cutoff scheme for new data calls is used. It is shown that the adequate model of this system is two-dimensional finite Markov chain. The state of space of the system is defined and a system of equilibrium equations is developed. It is proved that this system of equations has analytical solution in multiplicative form. An algorithm to calculate quality of service metrics of the proposed partition scheme based on given multiplicative solution is created. Results of numerical experiments are presented.